KUAT TEKAN BETON AKIBAT PENAMBAHAN ABU TEMPURUNG KELAPA - Ismael Samen; Jeffrey A. Delarue; Titof Tulaka, (Sustainable Construction (SUSCON), 2024)
Materials that cannot be reused are considered waste. But the majority of garbage can be recycled more successfully and effectively. Waste from coconut shells can be found in a variety of locations, including conventional markets, homes where food is processed, and stores that offer general merchandise. Since coconut shell ash is added to concrete, it is frequently used as a cooking burner or left to accumulate. However, because of this, coconut shell waste has not yet been completely utilized as an affordable resource to determine the compressive strength of concrete. Additionally, to get the best possible presentation of coconut shell ash on concrete's compressive strength. An average compressive strength of 32.006 Mpa is obtained from regular concrete without the addition of coconut shell ash (BN). An average compressive strength of 28.388 MPa is obtained by adding 2.5% coconut shell ash. An average compressive strength of 26,596 MPa is obtained by adding 5% coconut shell ash. An average compressive strength of 23.484 MPa is obtained by adding 7.5% of coconut shell ash. And an average compressive strength of 22,069 MPa is obtained by adding 10% of coconut shell ash. The concrete's compressive strength has not increased to its full potential despite the addition of coconut shell ash to the mixture.